Dynamic Sectoral Growth and Export Expansion Determinants: the Evidence from the Asian Countries - Ali, Eid (2000)
This research work is an empirical analysis of the effects of the outward orientation policies on economic growth of four of the Asian NICs, namely Korea Singapore, Malaysia and Thailand. The first research matter dealt with the impacts of the government policies in export, financial and government sectors on the economic growth, and the second research matter addressed the determinants of the export expansion in the studied countries. Basically the liberalization policies implemented in the export, financial, and government sectors, argued to have favorable effects on the efficiency of these sectors. The argument suggests that the marginal factor productivity in these sectors should be higher due to the policies implemented in these sectors. Thus, to investigate the efficiency of these sectors, the researcher extended a framework developed by Feder (1983) using neoclassical production function approach. The basic idea behind this framework is that, dividing the economy into two sectors first the proposed efficient sector output and the second is the rest of an economy output. Specifying the production function with assuming that the marginal factors productivity differential among an economy sectors allows testing for the efficiency differential among sectors. The researcher extended the two-sector model to include a third sector, that extend the scope of the framework to be usable for investigating the axiomatic macroeconomic rule that macroeconomic policies do not work in isolation, and met the study objectives. The results of estimation of the three-sector model showed that, export, financial and government sectors are efficient and the marginal factor productivity in these sectors is enhanced over the time and with the stage of development. The results also show that, export sector is not the only dominant sector as it is found in the previous studies, but also financial and government sectors are important in determining the long run economic growth of the studied countries. In the second research issue, the researcher attempted to investigate whether the export expansion is a demand or supply determinant. Utilizing export's demand and supply systems, the researcher also incorporates the exchange rate volatility to the demand equation. The results showed that both export demand and supply are important in determining export expansion in the studied countries and over the study period. However, exchange rate volatility had adversely effects on the export demand. The study utilized the last advancements made in the econometrics of the time series to ensure the robustness of the estimation of the models.